TERMS OF CONSIDERATION AND RESOLUTION OF CIVIL CASES BY GENERAL JURISDICTION COURTS (RUSSIAN EXPERIENCE) - Borisova, Elena (Teisė, 2016)
The article sets forth notes for the statement at the international scientific conference to commemorate 375 th anniversary of the Faculty and to finalise the national scientific project financed by the Research Council of Lithuania “Ways of implementation of the right to civil proceedings within a reasonable time”.